2009
DOI: 10.2106/jbjs.h.00768
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Surgical Preparation Solutions in Shoulder Surgery

Abstract: ChloraPrep is more effective than DuraPrep and povidone-iodine at eliminating overall bacteria from the shoulder region. Both ChloraPrep and DuraPrep are more effective than povidone-iodine at eliminating coagulase-negative Staphylococcus from the shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
178
3
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(192 citation statements)
references
References 10 publications
5
178
3
6
Order By: Relevance
“…First, our results are applicable only to shoulders because this was the only body part we studied; however, it is feasible that similar results would be found for other body regions because we think the ultrasound transmission gel or ultrasound probe can serve as a vector to transport bacteria from one area of skin to another. Second, our incubation period was only 5 days, and additional time may be required to cultivate certain pathogens that are particularly relevant to shoulder infections, such as Propionibacterium acnes [24]. Third, the effect of nonsterile gel on contamination was not assessed independent of sterile gel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, our results are applicable only to shoulders because this was the only body part we studied; however, it is feasible that similar results would be found for other body regions because we think the ultrasound transmission gel or ultrasound probe can serve as a vector to transport bacteria from one area of skin to another. Second, our incubation period was only 5 days, and additional time may be required to cultivate certain pathogens that are particularly relevant to shoulder infections, such as Propionibacterium acnes [24]. Third, the effect of nonsterile gel on contamination was not assessed independent of sterile gel.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is paucity of data regarding infection risk and colonization related to musculoskeletal injections, recommendations of preparatory agents for surgical procedures can be extrapolated for this purpose. Saltzman et al [24] reported that combination chlorhexadine and alcohol-based preparations were superior to combinations of iodine and alcohol-based preparations at decreasing overall bacterial colonization in patients undergoing shoulder surgery. This trend also was consistent specifically to species of staphylococcus but not P acnes [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when examining the studies used in the systematic review by Lee et al, 1 we see that the authors found only 3 studies (Saltzman et al, 3 Ostrander et al," and Veiga et al 5 ) that compared iodophore solutions that contain alcohol with chlorhexidine solutions that contain alcohol. In these studies, the outcomes measured were positive skin swab cultures and/or SSIs.…”
Section: The Importance Of Isopropyl Alcohol In Skin Preparation Solumentioning
confidence: 99%
“…3 The authors raise an interesting point, suggesting that the effectiveness of chlorhexidine-based formulations may be attributable to alcohol rather than to chlorhexidine. They include the following points in support of their hypothesis, which we appreciate having the opportunity to address below.…”
Section: Reply To Maiwald Et Al and Riccio Et Almentioning
confidence: 99%